When a Sex Offender Comes to Visit: A National Assessment of Travel Restrictions - Rolfe, Shawn M. (Criminal justice policy review, 2019)
The present study examines the registration requirements for registered sex offenders traveling from their resident state to another state for business or pleasure. The author contacted each state’s primary Sex Offender Registration and Notification (SORN) office to obtain the required registration requirements for nonresident sex offenders, as well as where and how nonresident sex offenders can obtain this information prior to visiting that state. The findings indicate that registration requirements and residence restrictions vary significantly by state for nonresident registrants. While not surprising given that numerous studies have highlighted that sex offender policies produce unique and severe challenges for all sex offenders in the United States. This study, however, suggests that nonresident sex offender policies are potentially another collateral consequences for registrants. Most notably, there is significant variation in the number of days a registered sex offender has to register in any given state when they come to visit for any occasion. Depending on the state or jurisdiction that the registrant is visiting, residence restrictions may also be applicable. As a result of these laws, registrants may feel stymied from visiting another state, which may further delineate prosocial opportunities, including gatherings with family and friends or fulfilling employment obligations. Additionally, states may experience an increased financial burden due to the manpower needed to enforce their state’s nonresident sex offender laws, especially in areas that are known tourist destinations. Future research and policy implications are further discussed.